Prognostic value of renal failure in patients undergoing transvenous lead extraction: single centre experience and systematic review of the literature. (2nd November 2022) - Massaro, Giulia; Spadotto, Alberto; Canovi, Luca; Martignani, Cristian; Ziacchi, Matteo; Angeletti, Andrea; Galie, Nazzareno; Boriani, Giuseppe; Biffi, Mauro; Diemberger, Igor
ABSTRACT: Introduction: Cardiac implantable electronic device infections (CIEDI) are challenging complications, associated with high mortality rate. Transvenous lead extraction (TLE) is the only curative treatment for CIEDI. Albeit continuous improvement in tools and techniques dramatically decreased TLE associated complications, survival after TLE for CIEDI is still poor. Renal failure (RF) is frequently reported in candidates to TLE, but due to variability in its definition, the real prevalence is not well defined. Objective: Considering the impact of RF on mortality among patients affected by cardiovascular diseases, we aimed our research at defining the role of RF as a predictor of post-TLE mortality. Method and Results: We will provide the results of a systematic revision of literature on the impact of RF on mortality at different time points after TLE, according to the various definitions adopted for RF. Considering the high variability of literature in this field, we will provide the results of an explorative analysis comparing the different definitions of RF on clinical outcomes in a cohort of candidates to TLE for CIEDI in a high-volume referral center. Conclusion: We discuss the possible reasons of the negative impact of RF after TLE, providing new perspectives for future research.